2021
DOI: 10.1007/s12652-020-02776-4
|View full text |Cite
|
Sign up to set email alerts
|

Seismic response prediction of FRC rectangular columns using intelligent fuzzy-based hybrid metaheuristic techniques

Abstract: This research study focused on the dynamic response and mechanical performance of fiber-reinforced concrete columns using hybrid numerical algorithms. Whereas test data has non-linearity, an artificial intelligence (AI) algorithm has been incorporated with different metaheuristic algorithms. About 317 datasets have been applied from the real test results to detect the promising factor of strength subjected to the seismic loads. Adaptive neuro-fuzzy inference system (ANFIS) was carried out as an AI beside the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(26 citation statements)
references
References 49 publications
(56 reference statements)
0
19
0
Order By: Relevance
“…As discussed comprehensively, ANFIS can be considered as a reliable predictive method to be integrated with other metaheuristics algorithms, like previous studies [28,43,44] which have used hybrid algorithms to solve non-linear relationships between input and output variables.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As discussed comprehensively, ANFIS can be considered as a reliable predictive method to be integrated with other metaheuristics algorithms, like previous studies [28,43,44] which have used hybrid algorithms to solve non-linear relationships between input and output variables.…”
Section: Discussion Of Resultsmentioning
confidence: 99%
“…Several AI-based models have been utilized to predict the hardened and fresh properties of concrete. Studies have revealed that using hybrid algorithms in many cases can lead to improving the performance of predictive models [43][44][45][46]. The main objective of this paper is to predict the SP demand of specific SCC by soft computing methods to avoid mathematical approaches with high nonlinearity.…”
Section: Introductionmentioning
confidence: 99%
“…Viana et al (2020) addressed a corotational Lagrangian formulation for nonlinear dynamic analysis of steel planar frames. Mehrabi et al (2021) studied the dynamic response and mechanical performance of fiber-reinforced concrete columns using hybrid numerical algorithms.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…The experimental test results of the wing-box were also compared with the predictions made by a numerical study performed. Mehrabi et al (2021) dealt with a seismic response prediction of fiber-reinforced concrete columns rectangular columns using intelligent fuzzy-based hybrid metaheuristic techniques.…”
Section: Literature Reviewmentioning
confidence: 99%